Evolution of groundwater chemistry on shallow aquifer of Yogyakarta City urban area - Doni Prakasa Eka Putra (Journal of Applied Geology, 2015)
Since 1980s, accelerated by urbanization, Yogyakarta City was shifting to many directions defined by main road networks and service centres. Urbanization has transformed rural dwellings to become urban settlements and generated urban agglomeration area. Until now, new business centres, education centres and tourism centres are growing hand in hand with new settlements (formal or informal) without proper provision of water supply and sanitation system. This condition increase the possibility of groundwater contamination from urban wastewater and a change of major chemistry of groundwater as shallow unconfined aquifer is lying under Yogyakarta City. To prove the evolution of groundwater chemistry, old data taken on 1980s were comparing with the recent groundwater chemistry data. The evaluation shows that nitrate content of groundwater in 1980s was a minor anion, but nowadays become a major anion, especially in the shallow groundwater in the centre of Yogyakarta City. This evidence shows that there is an evolution of groundwater chemistry in shallow groundwater below Yogyakarta City due to contamination from un-proper on-site sanitation system. Keywords: Urbanization, Yogyakarta city, rural dwellings, settlements, agglomeration, contamination, groundwater